The athletic heart syndrome - Puffer, J. C. (The Physician and Sportsmedicine, 2002)
Patients who participate in regular vigorous or strenuous physical activities undergo significant changes in cardiac structure and function. Occasionally, these changes may be confused with those of hypertrophic cardiomyopathy (HCM). Differentiating between athletic heart syndrome and HCM requires careful examination. ECG and echocardiograms may be helpful, but other techniques such as detraining can also be useful in resolving the issue. Detraining produces regression of cardiac features in patients with athletic heart syndrome, while enlarged cardiac features remain unchanged in those with HCM.